Effect of phosphoglucoisomerase (hasE) and hyaluronan synthase (hasA) co-expression on hyaluronic acid production in Escherichia coli rosetta (DE3) - Samsudin, Muhammad Azmi (2013)
Hyaluronic acid (HA) is one of nature’s most versatile and fascinating materials due to its unique behavior and characteristic. This substance has a wide usage in clinical sector and plays a very important role in physiological and cell biological functions. Previously, the main source of this polysaccharide was from animal, but due to ethical issues and viral contamination, bacteria has emerged as an alternative resource for HA. The utilization of bacteria to produce HA is further improved by using heterologous recombinant host such as Escherichia coli. This study was aimed to enhance the production and molecular weight of HA in a new recombinant E. coli host that posed useful industrial characteristic. Productions of hyaluronic acid were performed by expression of hyaluronan synthase (hasA) and phosphoglucoisomerase (hasE) genes in selected expression vectors into E. coli Rosetta (DE3) expression host. In this study, genomic DNA was isolated from Streptococcus zooepidemicus ATCC 39920. The hasA and hasE genes were succesfully PCR amplified using primers derived from NCBI GeneBank database. The fragments were then cloned into TOP 10 E.coli cloning vector. Sequencing results showed that both genes cloned were 100% identical to the published sequences. The inserts from the TOP 10 clones were sub-cloned into two different expression vectors, pRSF-DUET and pCDF. The hasA was cloned into pRSF-DUET, while hasE gene was cloned into both pRSF-DUET and pCDF producing pRSF-DUETA, pRSF-DUET-AE and pCDF-E. All clones were transformed into E. coli Rosetta (DE3). Four recombinant clones, E. coli Clone A, AE, A-E and AE-E were produced by transforming the recombinant plasmids into the expression host. All clones successfully expressed the recombinant proteins corresponding to the expected sizes of ~42 kDa and ~48 kDa. Both recombinant proteins were confirmed by western blotting using monoclonal anti-His and anti-S antibody. Batch cultivation of all clones in shake-flask showed a rapid decreased in cell growth after induction with Isopropyl β-D-1- thiogalactopyranoside (IPTG). The highest concentration and molecular weight of HA obtained were from clone AE-E at 30°C with the concentration of 0.072 g/L and a molecular weight of 1.1X105 Da.